Delphi-AHP Based Methodology for Selecting Causal Factors of Marine Transportation Accidents - Yacob, Mohd Najib; Hassim, Mimi Haryani (International Journal of Integrated Engineering, 2025)
The causal factors of marine transportation accident are important to be identified in order to minimize the number of accidents that are reported over the years. The objective of this study is to establish the priorities (importance) of causal factors in causing accidents involving marine transportation that handles hazardous materials (HAZMAT). Two methods were employed, which are the Delphi and the Analytical Hierarchy Process (AHP) methods. As part of these methods, ten professionals in marine safety in Malaysia, both from the industries and academia, were selected to weigh their expert judgments on the prioritization of the causal factors based on the safety aspect of the HAZMAT marine transportation operation. From the study, 26 factors were pre-determined as a result of the Delphi method application, which was then further categorized into three main aspects of environment, technical and management. Weightings of each aspect were calculated using the AHP method through Expert Choice 2000 software to determine the pair-wise comparison between evaluated aspects contributing to marine transportation accidents. The integrated Delphi-AHP method as proposed in this study was suitable for retrieving a more efficient decision- making process among the top management in planning a comprehensive safety assessment for maritime shipping industries.